Microbial Production Of Polyhydroxybutyrate (Phb) By Burkholderia Cepacia Bpt1213 From Different Carbon Sources And Its Fermentation Kinetics - Wen Chian, Liew (Pusat Pengajian Teknologi Industri, 2020)
The issue of plastic pollution has become a major threat to global ecology due to plastic’s resilience against degradation and its proliferation in industry. As a result, the biodegradable polymer such as polyhydroxyalkanoate (PHA) is considered as a good substitute to the conventional petroleum-based polymers because of their similar material properties to synthetic polymers and complete biodegradability after disposal. However, PHA homopolymer, poly-3-hydroxybutyrate (P(3HB)) is the most common and widely studied PHA compounds. In this study, the biosynthesis of P(3HB) polymer produced by Burkholderia cepacia BPT1213 using different carbon source such as banana trunk juices, molasses and oil palm frond juices was studied. Besides, the sugar contents (sucrose, glucose and fructose) of these carbon sources were analysed. Molasses has the highest sucrose, glucose and fructose content (8.41 ± 0.50 mg/mL, 35.34 ± 0.01 mg/mL and 33.88 ± 0.06 mg/mL respectively). Next, kinetic study of B. cepacia BPT1213 such as specific growth rate, doubling time, biomass and PHA productivity were investigated for greater understanding of the fermentation efficiency.